FIRST REPORT ON THE HPLC PROFILE, IN VITRO AND IN SILICO BIOACTIVITIES OF Arbutus unedo L. FRUIT ETHANOLIC EXTRACT FROM ALGERIA. - Wafa, Nouioua; Elkolli, Meriem; Elkolli, Hayet (Journal of the Chilean Chemical Society, 2025)
Arbutus unedo L., commonly known as the Strawberry tree, is gaining increasing interest due to its traditional, industrial, and medicinal applications. This study evaluates the in vitro and in silico biological activities of the ethanolic extract of A. unedo fruit, namely its antioxidant, anti-inflammatory and antibacterial properties. HPLC analysis was carried out for the determination of the main components of the extract. Antioxidant activity was assessed via DPPH radical scavenging method, ABTS, metal chelation and β-carotene/linoleic acid bleaching assays while the antiinflammatory activity was done via the inhibition of albumin denaturation method. The in vitro antibacterial activity was evaluated by the disk diffusion method against four ATTC strains. Molecular docking was performed using Autodock Vina PyRx docking techniques against ten bacterial protein targets. HPLC analysis identified 11 compounds whose majority components are: chlorogenic acid (22.66µg/mL) and gallic acid (15.43µg/mL). The extract exhibited strong antioxidant potential, with IC50 values of 0.1 ± 0.007 mg/mL for DPPH, 0.021 ± 0.02 mg/mL for ABTS, and 0.011 ± 0.006 mg/mL for iron chelation. The β-carotene/linoleic acid test showed inhibition rates ranging from 35.43% ± 0.03 to 89.42% ± 0.05. Additionally, the in vitro anti-inflammatory activity revealed an inhibitory effect of 92.97% compared to aspirin (97.40%) at 20 µg/mL. Naringenin, ellagic acid and chlorogenic acid are the best antibacterial candidates with binding energies of less than -8 kcal/mol and more bacterial targets bound. Ferulic acid, methyl gallate, caffeic acid, synergistic acid, and coumaric acid are the safest and pharmacokinetically favorable, while gallic acid, naringenin, and chlorogenic acid have limitations as toxicity or poor absorption. These findings support the traditional medicinal use of A. unedo and highlight its potential as a natural bioactive source.